Severe aortic stenosis without left ventricular hypertrophy: prevalence, predictors, and short-term follow up after aortic valve replacement. Issue 3 (September 1996) - Seiler, C.; Jenni, R.
Abstract : OBJECTIVES: The purpose of the present study in patients with severe aortic stenosis was to assess the prevalence of absent left ventricular hypertrophy (LVH) (determined according to mass criteria), to identify predictors of absent LVH, and to assess short-term left ventricular adaptation and prognosis after aortic valve replacement. METHODS: Left ventricular mass (LVM) was determined by echocardiography in 109 men and 101 women with severe aortic stenosis (mean pressure gradient < or = 50 mm Hg). LVH was defined as LVM > or = 109 g/m2 in women and LVM > or = 134 g/m2 in men. RESULTS: One hundred and eighty nine patients showed LVH (group 1) (90%; mean (SD) age 65 (14) years), and 21 showed no LVH (group 2) (10%, age 57 (21) years P = 0.02 for difference in age). Twelve (6%) of those without LVH had increased relative wall thickness (that is, > or = 0.45 with LV concentric remodelling) and nine (4%) showed no macroscopically detectable hypertrophic adaptation. The following variables were associated with the absence of LVH: low body surface area, low body mass index, and increased cardiac index. 76/210 patients were followed up a mean of six months after aortic valve replacement. The frequency of adequate ventricular adaptation to the decreased afterload after aortic valve replacement was higher in patients with LVH than in those without. Mortality six months after aortic valve replacement was lower, but not significantly, in patients with LVH (7.6%) than in those without LVH (12.5%, P = 0.10). CONCLUSIONS: A tenth of patients with severe aortic stenosis did not develop LVH according to mass criteria; 4% of the patients did not have any macroscopic signs of myocardial adaptation to the pressure overload despite longstanding disease. Small body size was independently associated with lack of LVH according to mass criteria. Six months after aortic valve replacement, ventricular adaptation was more often adequate in patients with LVH than in those without.